TOE1 acts as a 3′ exonuclease for telomerase RNA and regulates telomere maintenance. Issue 1 (29th October 2018) - Deng, Tingting; Huang, Yan; Weng, Kai; Lin, Song; Li, Yujing; Shi, Guang; Chen, Yali; Huang, Junjiu; Liu, Dan; Ma, Wenbin; Songyang, Zhou
Abstract: In human cells, telomeres are elongated by the telomerase complex that contains the reverse transcriptase hTERT and RNA template TERC/hTR. Poly(A)-specific ribonuclease (PARN) is known to trim hTR precursors by removing poly(A) tails. However, the precise mechanism of hTR 3′ maturation remains largely unknown. Target of Egr1 (TOE1) is an Asp-Glu-Asp-Asp (DEDD) domain containing deadenylase that is mutated in the human disease Pontocerebella Hypoplasia Type 7 (PCH7) and implicated in snRNA and hTR processing. We have previously found TOE1 to localize specifically in Cajal bodies, where telomerase RNP complex assembly takes place. In this study, we showed that TOE1 could interact with hTR and the telomerase complex. TOE1-deficient cells accumulated hTR precursors, including oligoadenylated and 3′-extended forms, which was accompanied by impaired telomerase activity and shortened telomeres. Telomerase activity in TOE1-deficient cells could be rescued by wild-type TOE1 but not the catalytically inactive mutant. Our results suggest that hTR 3′ end processing likely involves multiple exonucleases that work in parallel and/or sequentially, where TOE1 may function non-redundantly as a 3′-to-5′ exonuclease in conjunction with PARN. Our study highlights a mechanistic link between TOE1 mutation, improper hTR processing and telomere dysfunction in diseases such as PCH7.